2015
DOI: 10.1039/c4tc02428a
|View full text |Cite
|
Sign up to set email alerts
|

Structure transition and magnetism of bcc-Ni nanowires

Abstract: Body-centered-cubic (bcc) Ni nanowires were successfully synthesized by multistep ac electro-deposition on anodic aluminum oxide templates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The predicted lattice parameter for the Ni bcc lattice constant obtained in this way becomes 2.810, 2.797, and 2.805 Å for GGA, GGA-D3, and vdW-DF, respectively (Table II). The predicted values for the GGA and vdW-DF classes are in good agreement with the experimental data measured on nanosized bcc Ni particles ranging from 2.82-2.90 Å [56,57,61]. Applying the same scheme for predicting the bcc cohesive energy, i.e., using the correct experimental measure for fcc to predict the experimental cohesive energy for bcc, we obtain a difference between the fcc experimental and the bcc predicted values of 0.10 eV/atom for the GGA and the vdW-DF class of functionals, while the Grimme corrected functionals give 0.00 eV/atom.…”
Section: F Extrapolated Bcc Ni Lattice Constant Cohesive Energy Ansupporting
confidence: 85%
See 2 more Smart Citations
“…The predicted lattice parameter for the Ni bcc lattice constant obtained in this way becomes 2.810, 2.797, and 2.805 Å for GGA, GGA-D3, and vdW-DF, respectively (Table II). The predicted values for the GGA and vdW-DF classes are in good agreement with the experimental data measured on nanosized bcc Ni particles ranging from 2.82-2.90 Å [56,57,61]. Applying the same scheme for predicting the bcc cohesive energy, i.e., using the correct experimental measure for fcc to predict the experimental cohesive energy for bcc, we obtain a difference between the fcc experimental and the bcc predicted values of 0.10 eV/atom for the GGA and the vdW-DF class of functionals, while the Grimme corrected functionals give 0.00 eV/atom.…”
Section: F Extrapolated Bcc Ni Lattice Constant Cohesive Energy Ansupporting
confidence: 85%
“…Cohesive energies E coh for fcc Ni computed with the 11 different density functionals are given in Table SI of the Supplemental Material [52], which also includes Refs. [53][54][55][56][57][58]. The error calculated versus the experimental result extrapolated to 0 K (4.48 eV/atom) are shown in Fig.…”
Section: A Bulk Metals: Fcc and Bcc Nimentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic properties of Ni with BCC structure were questionable until Han et al investigated the magnetism of BCC-Ni nanowires in 2014. 65 Han et al demonstrated that the magnetic behaviors of BCC-Ni nanowires with a lattice constant of 0.288 nm were very different from the FCC-Ni nanowires and FCC-Ni bulks. The magnetization process of BCC-Ni involved the structure transition from BCC to FCC at 450 K. After the heat treatment at 773 K, the BCC-Ni nanowires transformed into the FCC structure.…”
Section: Discussionmentioning
confidence: 99%
“…7(b), it is shown that the cystalline structure of nanowires is a mixture of unreacted crystalline Sn and η−Cu 6 Sn 5 intermetallic compound. Due to conventional DC electrochemical deposition procedures, the growth of intermetallic compounds needs a post heat treatment step to facilitate the re-nucleation and growth of crystalline structures [65][66][67][68][69][70][71][72][73]. As a result, the observed intermetallic compound (η−Cu 6 Sn 5 , cref.…”
Section: Cu-sn Nanowiresmentioning
confidence: 99%